PENGARUH PELATIHAN STRUKURAL DAN PENGUASAAN TUGAS TERHADAP PRODUKTIVITAS KERJA PEGAWAI KECAMATAN SEKAR KABUPATEN BOJONEGORO - jurnalmap map; Susilo Utomo; Woro Utari; Cathrine Sri Hartati (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
ABSTRACT The purpose of this study is to describe training, job mastery and work creativity of employees. Then to train and measure performance both partially and simultaneously have a significant effect on employee work productivity. This type of research is explanatory research. The population in this study were all residents of Sekar District, Bojonegoro Regency who lived 31 people. The results showed that training and mastery of tasks simultaneously had a significant influence on work productivity in Sekar District, Bojonegoro Regency. Partial training and mastery of tasks have a significant influence on the work productivity of employees in the Sekar District, Bojonegoro Regency. Keywords: training, task mastery, work productivity